The Quality Characteristics Comparison of Stone-Milled Dried Whole Wheat Noodles, Dried Wheat Noodles, and Commercially Dried Whole Wheat Noodles - Mengdi Cai; Chunxia Shen; Yuhui Li; Shuangli Xiong; Feng Li (Foods, 2022)
To explore the quality differences between dried wheat noodles (DWNs), stone-milled dried whole wheat noodles (SDWWNs), and commercially dried whole wheat noodles (CDWWNs), the cooking quality, texture properties, microstructure, protein secondary structure, short-range order of starch, antioxidant activity, in vitro digestive properties, and estimated glycemic index (eGI) of the noodles were investigated. The results showed that the cooking loss of SDWWNs was significantly lower than that of CDWWNs. The springiness, cohesiveness, gumminess, chewiness, and resilience of SDWWNs reached the maximum, and the tensile strength was significantly increased. The continuity of the gluten network of SDWWNs was reduced, and more holes appeared. The protein secondary structure of the SDWWNs and CDWWNs was mainly dominated by the β-sheet and β-turn, and the differences in the starch short-range order were not significant. Prior to and after the in vitro simulated digestion, the DPPH radical scavenging activity, the hydroxyl radical scavenging activity, and the total reducing power of the SDWWNs were the highest. Although the digested starch content of SDWWNs did not differ significantly from that of CDWWNs, the eGI was significantly lower than that of the CDWWNs and DWNs. Overall, the SDWWNs had certain advantages, in terms of quality characteristics.